Direct and Alkaline Glycerol Liquefaction of Hazelnut Shell - Demirbaş, Ayhan (TAYLOR & FRANCIS INC, 2010)
Hazelnut shell was liquefied directly in water at 530–710 K and in glycerol and alkaline (10% sodium carbonate) glycerol at 523–603 K temperature range. Thermal degradation of biomass, cellulose, hemicelluloses, and products were formed as well as a solid residue of char in low temperatures. In the liquefaction process, the micellar-like broken down fragments produced by hydrolysis are degraded to smaller compounds by dehydration, dehydrogenation, deoxygenation, and decarboxylation. These compounds once produced, rearrange through condensation, cyclization, and polymerization, leading to new compounds. The yields of water liquefaction were 13.5, 21.0, 30.3, 32.3, 36.8, 45.4, 47.8, 48.4, and 46.3% by weight at 550, 570, 590, 610, 630, 650, 670, 690, and 710 K, respectively. Alkalis such as sodium carbonate and potassium carbonate, can lead to the formation of hydrolysis of macromolecules, such as cellulose and hemicellulose, into smaller fragments. The yields of alkaline glycerol liquefaction were 34.7, 39.5, 89.8, 98.4, and 100% by weight at 523, 533, 543, 553, and 563 K, respectively. The yields of liquid products slightly decreased at temperatures greater than 583 K. The yields of liquefaction were 96.8, 93.6, and 91.7% by weight at 583, 593, and 603 K, respectively.
Keywords: Alkali; Biomass; Glycerol; Hazelnut shell; Liquefaction